Haber and impersonality in Spanish: sociolinguistic and geolectal patterns - Manjón-Cabeza Cruz, Antonio; Svetozarovová, Radka (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Is Spanish, haber with existential value features cases of both discordance with its argument (hubo fiestas) or concordance (hubieron fiestas). RAE and ASALE (2009: 3063) point out that concordance of haber in plural is currently expanding in Spanish. Furthermore, Fernández Soriano and Táboas Baylín (1999) state that in Latin America, the concordance is the norm. These assertions must be weighed against the results of sociolinguistic studies, which have been numerous in both Spain and America. However, these are not easily comparable since they have been based on different corpora and methodologies. Only those studies that have been carried out based on the PRESEEA Project share variables and methodology. They can therefore provide us with more realistic materials of haber concordance in use. The results of these studies point to the fact that the categorical statements of the reference grammars of Spanish need to be qualified since the division between American and European Spanish is not the determining factor in the concordance rate.
Keywords: grammatical variation; concordant haber; sociolinguistics; PRESEEA